Isolation and characterization of a membrane protein from normal human erythrocytes that inhibits reactive lysis of the erythrocytes of paroxysmal nocturnal hemoglobinuria. - Holguin, M H (1989)
The observation that type III erythrocytes of paroxysmal nocturnal hemoglobinuria (PNH) are susceptible to hemolysis initiated by activated cobra venom factor complexes (CoFBb), whereas normal erythrocytes are resistant, implies that the PNH III cells are deficient in a membrane constituent that regulates this process. To isolate the inhibitory factor from normal erythrocytes, membrane proteins were first extracted with butanol and then subjected to sequential anion exchange, hydroxylapatite, and hydrophobic chromatography. Analysis by SDS-PAGE and silver stain of the inhibitory fractions showed a single band corresponding to a protein with an apparent Mr of 18 kD. PNH erythrocytes were incubated with incremental concentrations of the radiolabeled protein and then washed. In a dose-dependent fashion, the protein incorporated into the cell membrane and inhibited CoFBb-initiated lysis. This protein inhibitor functioned by restricting the assembly of the membrane attack complex at the level of C7 and C8 incorporation. By using a monospecific antibody to block the function of the inhibitor, it was shown that normal erythrocytes are rendered susceptible to CoFBb-initiated hemolysis. Analysis by Western blot of membrane proteins revealed that PNH III erythrocytes are deficient in the 18-kD protein. By virtue of its molecular weight and inhibitory activity, the 18-kD protein appears to be discrete from other previously described erythrocyte membrane proteins that regulate complement. These studies also indicate that the susceptibility of PNH III erythrocytes to reactive lysis is causally related to a deficiency of the 18-kD membrane inhibitor.